(untitled) (Research, Society and Development, 2021)
Objectives: Identify the practices adopted by men to prevent prostate cancer; describe the health behaviors of men affected with prostate cancer and discuss their impact on men’s lives. Methodology: Descriptive and exploratory study, with a qualitative approach, developed with 25 men aged 55 years and over, diagnosed with prostate cancer in the urological unit of a university hospital located in the city of Rio de Janeiro. The data collection instrument was the semi-structured interview and, for data analysis, the content analysis technique was applied, according to the following steps: pre-analysis, material exploration and treatment of results, inference and interpretation. Results and Discussion: The study showed that even understanding the need to take care of their health, through disease prevention, they only sought care when symptoms began to bother them in some way. This reinforces not only the deficit in self-care, but also the difficulty of perceiving oneself as vulnerable and responsible for one’s health. In addition, there are many feelings, expectations and meanings attributed by men after diagnosis, especially those involving sexual practice. Final considerations: It is essential to embrace it in its entirety in the gender perspective, thus bringing a challenge to think about men’s health aimed at promoting health and preventing diseases, establishing health education as a pillar to strengthen the link of the male population with health services.